PEMANFAATAN MINYAK JELANTAH MENJADI SABUN UNTUK MASYARAKAT DESA PENTUKREJO - Hermawan, Hengki; Sayekti, Ika Candra; Nurhandayani, Fitria Bekti; Tadzkiroh, Ummi (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2020)
The aim of this service is to provide knowledge to the Pentukrejo village community about the dangers of using used cooking oil and use it as dishwashing soap, cloth, and instill in the community about loving the environment and providing skills to the community to gain experience in making soap. So that it can be used as a business if made in large quantities. The community service participants were PKK women from Pentukrejo village. The implementation method of the service includes preparation, implementation (presentation, making practice, mentoring), and reporting. The result of this dedication is to provide knowledge about the use of used cooking oil into washing soap and providing knowledge about the dangers of used cooking oil for health and the environment. From this dedication, it is hoped that the people of Pentukrejo village can use used cooking oil to make laundry soap and it can apply love for the environment and love for body health.